2020
DOI: 10.1088/1361-6552/aba107
|View full text |Cite
|
Sign up to set email alerts
|

Examining Grade 11 science students’ difficulties in learning about vector operations

Abstract: Studies on student learning of scientific concepts have shown that students often experience various difficulties in understanding basic physics concepts such as vector quantities, as a result of formal and informal learning. The purpose of the present study is to document Grade 11 students’ difficulties in understanding vectors and their associated concepts. Specifically, the study tried to find answers to ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 32 publications
(77 reference statements)
0
7
0
2
Order By: Relevance
“…Knight studied the qualitative as well as quantitative knowledge of students for vectors. A study [10] conducted on 11th-grade students suggested that most students had difficulties in graphical and analytical vector addition, vector multiplication and determining magnitude and direction of vectors. Numerous incorrect preconceptions among high school students about the role and significance of the velocity vector components have been reported [11].…”
Section: Previous Research On Students' Difficulties With Vectorsmentioning
confidence: 99%
“…Knight studied the qualitative as well as quantitative knowledge of students for vectors. A study [10] conducted on 11th-grade students suggested that most students had difficulties in graphical and analytical vector addition, vector multiplication and determining magnitude and direction of vectors. Numerous incorrect preconceptions among high school students about the role and significance of the velocity vector components have been reported [11].…”
Section: Previous Research On Students' Difficulties With Vectorsmentioning
confidence: 99%
“…Sierpinska et al (1999) conciben al vector como una invariante de representaciones, interpretada en el contexto de la física como dibujos de flechas que representan fuerzas y sus combinaciones actuando sobre objetos. Sin embargo, vector es un concepto matemático del cual se ha documentado que estudiantes de diferentes niveles educativos tienen dificultades, tales como: trabajar con su representación gráfica, distinguir entre suma y resta de vectores, determinar su dirección y calcular su magnitud (Barniol & Zavala, 2014a;Carli et al, 2020;Latifa et al, 2021;Tairab et al, 2020). En particular, se ha reportado que algunas dificultades con el concepto vector se originan en nivel básico secundaria (12-15 años), ya que los estudiantes no desarrollan suficientes habilidades en torno a dicho concepto (Flores-García et al, 2007).…”
Section: Introductionunclassified
“…The UAE has engaged in online education to cope with the challenges caused by the pandemic. Due to the abstract nature of physics concepts which may require high cognitive ability to comprehend as suggested by Tairab et al (2020), physics content would be more difficult for students to master through online learning. In addition, Sari et al (2019) argued that the mathematical complexity of physics can quickly overwhelm students' intuition.…”
Section: Introductionmentioning
confidence: 99%